Anesthesia Capacity of District-Level Hospitals in Malawi, Tanzania, and Zambia: A Mixed-Methods Study. (April 2020) - Gajewski, Jakub; Pittalis, Chiara; Lavy, Chris; Borgstein, Eric; Bijlmakers, Leon; Mwapasa, Gerald; Cheelo, Mweene; Le, Grace; Juma, Adinan; Kachimba, John; Marealle, Paul; Mkandawire, Nyengo; et al.
Abstract : BACKGROUND: District-level hospitals (DLHs) are the main providers of surgical services for rural populations in Sub-Saharan Africa (SSA). Skilled teams are essential for surgical care, and gaps in anesthesia impact negatively on surgical capacity and outcomes. This study, from a baseline of a project scaling-up access to safe surgical and anesthesia care in Malawi, Tanzania, and Zambia, illustrates the deficit of anesthesia care in DLHs. METHODS: We undertook an in-depth investigation of anesthesia capacity in 76 DLHs across the 3 countries, July to November 2017, using a mixed-methods approach. The quantitative component assessed district-level anesthesia capacity using a standardized scoring system based on an adapted and extended Personnel, Infrastructure, Procedures, Equipment and Supplies (PIPES) Index. The qualitative component involved semistructured interviews with providers from 33 DLHs, exploring how weaknesses in anesthesia impacted district surgical team practices and quality, volume, and scope of service provision. RESULTS: Anesthesia care at the district level in these countries is provided only by nonphysician anesthetists, some of whom have no formal training. Ketamine anesthesia is widely used in all hospitals, compensating for shortages of other forms of anesthesia. Pediatric size supplies/equipment were frequently missing. Anesthesia PIPES index scores in Malawi (M = 8.0), Zambia (M = 8.3), and Tanzania (M = 8.4) were similar ( P = .59), but an analysis of individual PIPES components revealed important cross-country differences. Irregular availability of reliable equipment and supply is a particular priority in Malawi, where only 29% of facilities have uninterrupted access to electricity and 23% have constant access to water, among other challenges. Zambia is mostly affected by staffing shortages, with 30% of surveyed hospitals lacking an anesthesia provider. The challenge that stood out in Tanzania was nonavailability of functioning anesthesia machines among frequent shortages of staff and other equipment. CONCLUSIONS: Tanzania, Malawi, and Zambia are falling far short of ensuring universal access to safe and affordable surgical and anesthesia care for district and rural populations. Mixed-methods situation analyses, undertaken in collaboration with anesthesia specialists—measuring and understanding deficits in district hospital anesthetic staff, equipment, and supplies—are needed to address the critical neglect of anesthesia that is essential to providing surgical responses to the needs of rural populations in SSA.